Bibliometric analysis on the implementation digitization technologies in cultural heritage in Malaysia - Siti Zuliana Salleh; A.R. Bushroa (Penerbit Universiti Kebangsaan Malaysia, 2022)
Malaysia is a rich country with significant tangible and diverse intangible cultural heritage assets. The cultural heritage information must be collected in order to transmit the information to future generations. In this digital era, knowledge transmission can be easily spread using digital platforms. Furthermore, the post-Covid-19 pandemic driven necessity of digital sharing platforms. However, the status of digital cultural heritage in Malaysia is unknown. Hence, this paper will be addressed the digitization of cultural heritage implementation in Malaysia based on the published research articles. The data extracted from the Web of Science and Scopus database has been analysed using bibliometric analysis. The search keywords related to the digitization of cultural heritage has extracted about 171 documents over 15 years of publication. This finding is significant to provide local researchers and related institutions with the potential of digital cultural heritage in a post-Covid-19 pandemic. The large potential of digital cultural heritage should motivate local researchers to increase the attention on digitization cultural heritage research area. Many potential applications which are benefited cultural heritage tourism, sustainability as well as contribution to the economy. The findings from this research indicate that the trend of digitization in the cultural heritage field needs to be strengthened.